Effects of Daily Δ(9)-Tetrahydrocannabinol (THC) alone or combined with Cannabidiol (CBD) on Cognition-based Behavior and Activity in Adolescent Nonhuman Primates - Withey, Sarah L. (Drug Alcohol Depend, 2021)
BACKGROUND: Daily use of marijuana is rising in adolescents, along with consumption of high potency marijuana products (high % Δ−9-tetrahydrocannabinol or THC). These dual, related trends have opened gaps in understanding the long-term effects of daily consumption of a high dose of THC in adolescents and whether a therapeutic dose of cannabidiol (CBD) modulates THC effects. METHODS: Adolescent squirrel monkeys (Saimiri boliviensis) were treated daily for four months with vehicle (n=4), a high THC dose (1 mg/kg i.m.; n=4), or THC + CBD (1 mg/kg + 3 mg/kg i.m.; n=4), to investigate whether: (1) a daily high THC dose affects performance in tasks of cognition (repeated acquisition, discrimination reversal); (2) a daily high THC dose affects spontaneous behavior and day/night activity (3) tolerance develops to the behavioral effects of THC; (4) whether CBD modulates THC effects. RESULTS: THC impaired performance of adolescent monkeys in a cognitive test initially, but not performance on a task of cognitive flexibility. THC reduced motor activity and increased sedentary behavior, with tolerance developing after weeks of daily treatment. Co-administered with THC, CBD did not modulate THC effects on cognitive performance, activity or tolerance, but prevented THC-induced emesis on the first day of daily treatment. CONCLUSIONS: Daily high dosing with THC compromised performance on a task of cognition, and reduced activity in adolescent primates, with tolerance developing within weeks. Whether our observations are relevant to a broader range of cognitive tasks vital for daily function in in human adolescents is uncertain.